PENGARUH SIKAP, KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN, PENGETAHUAN PERPAJAKAN, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI KASUS DI KECAMATAN SARADAN KABUPATEN MADIUN) - Nurhana Nurhana; Siti Suharni; Arini Wildaniyati (Universitas Merdeka Madiun, 2023)
This study aims to examine the effect of attitude, taxpayer awareness, service quality, tax knowledge and tax socialization on taxpayer compliance in paying land and building taxes. This type of research is quantitative research. Data collection techniques in this study used questionnaires directly to respondents. The sampling method in this study used purposive sampling with a total of 100 respondents in 10 (ten) villages in Saradan District. Data analysis was performed using multiple linear regression analysis using the SPSS (Statistical Product and Service Solution) version 25 for windows program. The results of the research hypothesis show that the independent variable of taxpayer attitude is 0,000, the independent variable is taxpayer awareness of 0,592, the independent variable of service quality is 0,259, the independent variable of taxation knowledge is 0,823, the independent variable of tax socialization is 0,000 and Adjusted R Square shows a value of 0,793 or 79,3%. The results of this study indicate that the attitude of taxpayers has an effect on taxpayer compliance, taxpayer awareness has no effect on taxpayer compliance, service quality has no effect on taxpayer compliance, tax knowledge has no effect on taxpayer compliance, and tax socialization has an effect on taxpayer compliance.